2019
DOI: 10.1002/mpr.1782
|View full text |Cite|
|
Sign up to set email alerts
|

Barriers of mental health treatment utilization among first‐year college students: First cross‐national results from the WHO World Mental Health International College Student Initiative

Abstract: Background Although mental disorders and suicidal thoughts‐behaviors (suicidal thoughts and behaviors) are common among university students, the majority of students with these problems remain untreated. It is unclear what the barriers are to these students seeking treatment. Aims The aim of this study is to examine the barriers to future help‐seeking and the associations of clinical characteristics with these barriers in a cross‐national sample of first‐year college st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
197
1
7

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 256 publications
(219 citation statements)
references
References 46 publications
(63 reference statements)
14
197
1
7
Order By: Relevance
“…Another important finding is that one third (34.5%) of the participants indicated that they would not be willing to utilize traditional available treatment formats such as face‐to‐face psychotherapy, further highlighting the potential of internet‐based treatments for reaching people who were previously not reached by the current health care system (Ebert, Van Daele, et al, ). This finding is in line with studies on barriers of treatment utilization in university students that found attitudinal barriers, such as a preference for self‐help or fear of stigma, to be more relevant than structural barriers, such as non‐availability, high costs, or long waiting times, in both university students (Ebert, Mortier, et al, ) and general population samples (Andrade et al, ).…”
Section: Discussionsupporting
confidence: 87%
“…Another important finding is that one third (34.5%) of the participants indicated that they would not be willing to utilize traditional available treatment formats such as face‐to‐face psychotherapy, further highlighting the potential of internet‐based treatments for reaching people who were previously not reached by the current health care system (Ebert, Van Daele, et al, ). This finding is in line with studies on barriers of treatment utilization in university students that found attitudinal barriers, such as a preference for self‐help or fear of stigma, to be more relevant than structural barriers, such as non‐availability, high costs, or long waiting times, in both university students (Ebert, Mortier, et al, ) and general population samples (Andrade et al, ).…”
Section: Discussionsupporting
confidence: 87%
“…The shame or guilt of binge-eating could be one explanation for not going to see a GP [ 41 ]. Given that the preference to handle problems alone and stigma appear to be critical, there could be a value in determining internet-based psychological treatments, which can be accessed privately and are often built as self-help approaches [ 42 ]. A meta-analysis showed a beneficial effect of internet interventions for mental health in university students on global eating disorder symptoms, weight concerns, and affective symptoms [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…mHealth (mobile health care), the delivery of mental health treatment using smartphones and wearables, presents an opportunity to narrow the research-practice gap by addressing barriers to treatment at the individual level. Indeed, recent research suggests that the most common reasons for not seeking mental health treatment are respondents' desire to manage their problems on their own, stigma associated with seeking psychological help, and perceptions of treatment as inconvenient or ineffective [11][12][13]. On the other hand, mobile health apps incorporate unique features that have the potential to circumvent the aforementioned barriers.…”
Section: Introductionmentioning
confidence: 99%